Quantitative evaluation of organosilane-based adhesion promoter effect on bitumen-aggregate bond by contact angle test. (January 2017) - Oliviero Rossi, Cesare; Caputo, Paolino; Baldino, Noemi; Szerb, Elisabeta Ildyko; Teltayev, Bagdat
Abstract: The performances of a modified bitumen as a function of the concentration of an added organosilane modifier was examined in terms of its consistency, adhesion and rheological properties. In particular, the modifier guarantees excellent performance at 0.01 wt% loading, and almost complete resistance to water at 0.03 wt% loading. A quantitative evaluation of the modified bitumen's performance was carried out by a contact angle test. Moreover, SEM/EDS analysis showed that the organosilane modifier was able to penetrate the surface of the stone, thus aiding anchoring of the binder to the surface.